Implementation of Digital Marketing with SEO on Gogalas Website for Business Directory Listing - Indri Sulistianingsih; Ahmad Akbar; Nova Maya Sari; Astri Mutia Rahma (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2023)
Gogalas is a website-based application that serves as a directory listing for services and products of small and medium enterprises in the village. The implementation of digital marketing with search engine optimization (SEO) has been applied to improve the visibility and searchability of the website. The purpose of this study is to determine the effectiveness of implementing digital marketing with SEO in improving the website's search engine rankings and visibility. The research method used in this study is descriptive quantitative research with data collection techniques through observation and documentation. The research data was analyzed using a comparative descriptive analysis technique to compare the website's search engine rankings and visibility before and after implementing digital marketing with SEO. The study results showed a significant improvement in the website's search engine rankings and visibility after implementing digital marketing with SEO. The website's visibility increased by 76,59% visitor bounce ratio in line with organic search in the search engine results page (SERP). This proves that implementing digital marketing with SEO is an effective method for improving and visibility of the Gogalas website.